ANALISIS RETURN MINGGUAN SAHAM KELOMPOK LQ 45 DI PT BURSA EFEK JAKARTA DENGAN MENGGUNAKAN ANALISIS FRAKTAL - Anthony Wijaya, Farolan
Abstract : Fractal Market Hypothesis (FMH) concept turns up in the capital markets as an alternative theory for Efficient Market Hypothesis (EMH) concept, it can see the weaknesses of portfolio modern concept. The EMH concept assumes that rational investors, efficient markets and random walks. This research is intended to identify wether the EMH concept is still suitable for the LQ45 stocks return or applies to the Hurst process which is biased random walk in nature and which is in accordance with the FMH concept emphasizing the effect of the liquidity and the horizon of the investor behavior. FMH concept uses the analysis of Rescaled Range (R/S) as a statistical processing tool and Hurst value used to measure the degree of risk. Higher value of Hurst (H) means less risky because the system is more persistent with less noise and clearer trend. The result of skewness, kurtosis, chi square test and the time structure of volatility test against weekly LQ45 stock returns from the period I: 1997 until period II 2001 showed that the assumption of the EMH concept was no in accordance with LQ45 stocks market. And from the analysis of the FMH concept, Matahari Putra Prima\'s stock had the highest value of Hurst (H=0.776) and the lowest ? ( ? =1.289). That means it has the lowest degree of risk and the highest correlation (C=46.5%). It is followed by Semen Gresik\'s stock, Telkom\'s stock, Bimantara Citra\'s stock, Kalbe Farma\'stock, Indosat\'s stock, Astra International\'s stock, HM Sampoerna\'s stock, Citra Marga NP\'s stock, Timah\'s stock, Indofood SM\'s stock, Ramayana LS\'s stock, Lippo Bank\'s stock. Gudang Garam\'s stock has the lowest Hurst value and the highest ? (H=0,57; ? =1,749;C=10,4%). On the basis of the inconsistency between the assumption of EMH concept and the weekly stock return of LQ45, the market that takes place at JSX is closer to the FMH concept. The FMH concept uses the biased random walk, investors consisting of various investment horizons and the correlation of the changing return stock from time to time.